Investigation of motivation based on Herzberg's two-factor model and self-determination theory - Dajnoki, Krisztina; Ujhelyi, Mária; Filep, Roland (Studia Mundi – Economica, 2021)
Nowadays, the appreciation of human resources is a global phenomenon, the issue of motivation and incentive within traditional HR functions is a popular and challenging area. In our study, we aimed to examine the factors that determine the motivation of the employees of a service organization. To this end, we analysed Herzberg’s two-factor model and the factors of the Self-Determination Theory. We sought to answer the question of whether workplace attachment and a good workplace atmosphere really appear to be as important key factors as the current literature analyses show. We asked workers what of the characteristics in the Herzberg model they consider important for an ideal workplace and what the current workplace provides an opportunity to address the three psychological needs in Self-Determination Theory. Based on the results of the regression analysis, we found that “encouraging creative, independent work” and “ensuring individual professional development” are positively related to motivation, with the “importance of basic wages” showing an inverse relationship with this. Examining the latter with the variable “work done, balance of wages received” by correlation calculation, it can be stated that the relationship between the variables is reversed, ie the higher the wage demand, the smaller the perceived balance in relation to the work performed. Respondents believe they do more for the organization than they receive from it. Based on the results, in order to maintain and increase the motivation of the employees in the examined organization, the managers must pay attention to providing the subordinates with the opportunity not only for continuous professional development but also for independent, creative work. Increasing wages, according to Herzberg, is not a motivator, but a hygienic factor, so it has no effect on satisfaction, thereby increasing motivation, but it can reduce dissatisfaction, so managers should take care of this, as well. The situation is similar in case of good workplace relationships, which, although was not included in the regression model, but received the highest mean values in both models.